A New Means to Generate Liposomes by Rehydrating Engineered Lipid Nanoconstructs - Yuqi Huang; Ziqian Xu; Umit Celik; Christopher F. Carnahan; Roland Faller; Atul N. Parikh; Gang-yu Liu (Micromachines)
The concept and feasibility of producing liposomes by rehydrating engineered lipid nanoconstructs are demonstrated in this study. Nanoconstructs of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) were produced using a microfluidic delivery probe integrated with an atomic force microscope. The subsequent rehydration of these POPC constructs led to the formation of liposomes, most of which remained adhered to the surface. The size (e.g., diameter) of the liposomes could be tuned by varying the lateral dimension of the lipid constructs. Hierarchical liposomal structures, such as pentagons containing five liposomes at the corners, could also be designed and produced by depositing lipid constructs to designated locations on the surfaces, followed by rehydration. This new means allows for regulating liposomal sizes, distributions, and compositions. The outcomes benefit applications of liposomes as delivery vehicles, sensors, and building blocks in biomaterials design. The ability to produce hierarchical liposomal structures benefits numerous applications such as proto-cell development, multiplexed bio-composite materials, and the engineering of local bio-environments.